The Influence of Facilities, Menu, and Marketing Strategy on Consumer Purchase Interest at Sae Space & Food Cafe In Boyolali - Siti Maesaroh; Rini Adiyani; Zandra Dwanita Widodo (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the influence of facilities, menu, and marketing strategies on consumer purchase intention at SAE Space & Food Café in Boyolali. This research uses a quantitative approach with a causal associative method. Data were collected through questionnaires distributed to 100 respondents who were customers of the café. The data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) using SPSS software. The results show that facilities have a positive and significant effect on consumer purchase intention with a significance value of 0.000. The menu also has a positive and significant effect with a significance value of 0.010. Marketing strategy has a positive and significant effect with a significance value of 0.018. Simultaneously, facilities, menu, and marketing strategies significantly influence consumer purchase intention with a significance value of 0.000. The Adjusted R Square value of 0.293 indicates that these three independent variables explain 29.3% of purchase intention, while the remaining percentage is influenced by other factors not examined in this study. In conclusion, facilities, menu quality, and effective marketing strategies are important factors in increasing consumer purchase intention at SAE Space & Food Café in Boyolali.